ANALISIS KUALITAS SPAREPART PIPA PADA PRODUKSI MESIN FIILING UNTUK MENGURANGI JUMLAH CACAT STUDI KASUS DI PT XYZ - Fandra Zakariyah; Muslimin Abdulrahim (LPPM Universitas Bina Bangsa, 2023)
Rapid development in the business world and increasingly advanced economic development that causes various problems in the industry, but the company does not stop there because in reality there are still products that do not meet the specifications that have been determined or defective products. In the flow of the production process, filling machines experience several defects in the product production process which often experience defects in the pipe production section. From these data can later be identified the most types of defects and the level of characteristics using pareto diagrams, and the cause and effect of the production process. Statistical Process Control (SPC) explains that this tool is used to continuously monitor the production process on an ongoing basis and identify damage that occurs during the production process. Based on the results of the retro diagram, it was concluded that 32.2% of the number of defects in the production of filling machines in pipe product parts, namely leaky pipes. i.e. the process at the operator's work is less than the procedure. Companies have standards but the behavior of workers who lack discipline in carrying out their work during the production process (work method)